2010
DOI: 10.1111/j.1532-5415.2010.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Glucose Tolerance and Lower Prevalence of Metabolic Syndrome in Offspring without Diabetes Mellitus of Nonagenarian Siblings: The Leiden Longevity Study

Abstract: Despite similar body composition, the offspring of nonagenarian siblings showed a lower prevalence of metabolic syndrome and better glucose tolerance than their partners, centralizing the role of favorable glucose metabolism in familial longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 26 publications
4
84
5
Order By: Relevance
“…In contrast to other cross-sectional studies that have included the offspring of centenarians or of nonagenarian siblings [3][4][5][6][7], we applied less rigid criteria to define longevity in the present study. Even having only one parent who had died at age 80 or later was associated with a reduced prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to other cross-sectional studies that have included the offspring of centenarians or of nonagenarian siblings [3][4][5][6][7], we applied less rigid criteria to define longevity in the present study. Even having only one parent who had died at age 80 or later was associated with a reduced prevalence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors may also contribute to better profiles of diabetes risk factors in the offspring of long-lived families: In a rather small study group, the offspring of Ashkenazi Jewish centenarians were shown to have inherited more favourable lipid profiles [15], and a reduced prevalence of hypertension was observed in the offspring of nonagenarian siblings and the offspring of centenarians [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-lived men exhibit several biological markers indicative of greater insulin sensitivity, which is associated with the FOXO3A GG genotype (Willcox et al 2008). Also, a favorable glucose metabolism is associated with familial longevity (Rozing et al 2010). Here, we failed to detect any significant association between the two FNDC5 SNPs we studied and EL, suggesting that other factors (e.g., maybe physical activity levels throughout lifespan, nutritional habits or complex gene-environment associations that are yet to be determined) might have a stronger influence on irisinemia, despite the potential functional consequence of at least one of the two SNPs we studied (i.e., rs726344).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, individuals with outlying cell counts (beyond 3 SDs below or above the standard error of the mean) were excluded. This subpopulation is representative for the whole LLS regarding disease prevalence and parameters involved in metabolic syndrome (Supplementary Table S5) Rozing et al, 2010). From these non-fasted individuals, peripheral blood was harvested using PAXgeneTM tubes (Qiagen, Venlo, the Netherlands).…”
Section: Sample Collection and Rna Preparationmentioning
confidence: 99%